Food insecurity and food pantry use among transgender and gender non-conforming people in the Southeast United States - Jennifer Russomanno; Jennifer M. Jabson Tree (BMC, 2020)
Abstract Background Transgender and gender non-conforming (TGNC) people face high rates of poverty, joblessness, and homelessness, rendering this population vulnerable to experiencing food insecurity. Yet, there is almost no empirical evidence concerning food insecurity and the use of local and federal food assistance resources in the TGNC community. Food insecurity, the use of local and Federal food assistance resources, and associations with gender-related minority stressors and resilience using the Gender Minority Stress and Resilience (GMSR) scale among TGNC individuals living in the Southeast United States (U.S.) were documented in this study. Methods A cross-sectional online survey was conducted with TGNC people living in the Southeast U.S. Participants were recruited via targeted Facebook advertisements. Results In total, 105 TGNC people completed the survey; 79% of survey participants experienced food insecurity, 19% utilized Federal, and 22% utilized local food assistance resources. High levels of minority stress and community resilience were reported. The GMSR resilience scale Pride (aOR = 1.09, 95% CI 1.00-1.19, p = .04) was significantly associated with the use of local food pantries, but minority stressors were not. No significant associations were found between GMSR and food security. Conclusion TGNC people living in the Southeast U.S. experienced food insecurity, unstable housing, low wages, and social stigma that were a barrier to using emergency food resources. Multi-level public health solutions that address discriminatory legislative policies and create linkages between TGNC people and local and federal food assistance are required to address issues of food insecurity in the TGNC population.